Dynamics of marketability structure of coppice oak stands in Slobozhanskyi forest typological district - Girs, O. A.; Pasternak, V. P.; Slysh, O. A. (Forestry and Forest Melioration, 2021)
Introduction Oak forests play an essential role in soil and water protection; they perform recreational and health-improving functions and also supply timber resources. According to the state forest records of Ukraine, as of January 1, 2011, English oak (Quercus robur L.) stands are among the most common stands in Ukraine: they cover an area of over 2,910 thousand hectares, or 28% of the forest fund of Ukraine. Oak timber is valuable for the national economy, primarily due to the possibility to obtain plywood logs. Therefore, it is important to determine the dynamics of marketability structure of oak stands. In Slobozhanskyi forest typological district, natural oak stands cover an area of over 180,000 hectares. They mainly have a density of stocking of 0.7. At the same time, after the age of 80, the density of stocking decreases. In coppice stands the proportion of the area of oak stands of the II site index class is 66.7%. According to the data as of 01.01.2017, oak forests were dominated by natural coppice stands, the percentage of which was 57 %; the proportion of planted stands was 36 %. The proportion of natural forests of seed origin was only 7 %. The largest area is occupied by coppice stands aged 81–120 years (65.3 %). Therefore, the development of standards for the marketability structure of coppice oak stands, with regard to their regional characteristics, is essential to provide sustainable management in them. M. V. Davydov compiled tables of the growth of fully-stocked seed and coppice oak stands and the dynamics of marketability of seed oak stands. The disadvantage of these tables is that they were designed for a large area and do not take into account regional peculiarities of stands. Our previous studies have shown that, in oak stands, the distribution of trees by diameter corresponds to the ?-distribution. The aim of the study was to establish the features of the dynamics of the marketability structure of coppice oak stands in Slobozhanskyi forest typological district. Materials and Methods According to forestry zoning, Slobozhanskyi district of the fresh-type forest typological region covers most of the Left-Bank Forest-Steppe in Ukraine. According to the physical and geographical zoning, the territory of the study region belongs to the Eastern Ukrainian and Left-Bank-Dnieper regions of the Forest-Steppe zone. For a detailed study of the marketability structure, 28 sample plots were laid out in coppice oak stands, on which 256 model trees were measured. Additionally, the data of sample plots were used, which were established under the guidance of M. V. Lyubchych with the measurement of 20 model trees. The analysis of sample plots according to the main indicators confirms that the stands selected for the study by their origin, composition, productivity, density of stocking and forest types meet the most typical conditions for the formation of oak stands in the Left-Bank Forest-Steppe in Ukraine. The results of the field and laboratory studies were processed using MS Excel, STRUC and Statistica applications. In order to identify the patterns of distribution of mensuration indicators for oak stands and to determine the homogeneity of the sample data, their statistical analysis was performed. The analysis of statistical indicators shows that the indicators of skewness and kurtosis do not exceed the allowable values in natural quantities for the average diameter and average height. Left-sided skewness was determined for age and height while right-sided one for other studied indicators. The distribution of age, average diameter and average height is characterized by a sharp-topped curve; blunt-topped curve was observed for density of stocking. The studied database of sample plots sufficiently fully describes the English oak forest stands and is suitable for modelling the evaluation and marketability structure. Analysis of correlation coefficients confirms a close relationship between such characteristics as average age, average diameter, and average height. The corresponding correlation coefficients range from 0.62 to 0.70. Theoretical series of trees distribution by diameter were built according to the method developed at the Department of Forest Taxation and Forest Management, NULES of Ukraine. Results In the study region, the English oak stands are characterized by average productivity; medium-stocked stands are most common. The relationship between the proportion of marketable trunks and the age of modal coppice oak stands was established as a function of average age. Regularities of the evaluation structure make a theoretical basis for the development of standards (tables of marketability structure and dynamics of marketability). To model the dynamics of the marketability structure of coppice oak stands we used regional growth tables, tables for distribution of the volume of marketable oak trunks by dimensional classes and parameters of the structure of stands by diameter. Dimensional classes of marketable timber were established on average diameter of logs without bark: D1b: 14.5–19.4 cm, D2: 19.5–29.4 cm, D3: 29.5–39.4 cm, D4:39.5–49.4 cm, D5: 49.5–59.4 cm. It should be noted that the standards for the marketability structure dynamics of modal oak stands are based on fundamentally new data on the distribution of marketable trunks of 16 cm and more by dimensional classes, consistent with European approaches to evaluation of round timber (DSTU EN 1316-1: 2001, 2019). A comparative analysis of the dynamics of marketable timber volume in modal coppice oak stands according to different standards (evaluation of marketable timber by upper and middle diameters) showed that the volume of marketable timber calculated by middle diameter is higher (by 14.7% on average), and the greatest difference is observed at younger stands. This is due to the fact that category D of marketable timber partially includes timber, which, according to the old standards, was considered as technological raw material. When comparing the standards developed for Slobozhanskyi forest typological district with the standards developed for seed oak stands, it should be noted that in the latter the volume of marketable timber is significantly higher, due to the peculiarities of the formation of stands in the study region and coppice origin. Conclusions The coppice oak stands of the study region differ significantly from the seed ones in terms of growth dynamics and marketability. Therefore, the norms of marketability structure dynamics for modal oak stands presented in this work, being consistent with European approaches to round timber evaluation, can significantly improve forest management and the accuracy in determining the marketability structure of oak stands in Slobozhanskyi region. Both the findings and production inspection confirmed the efficiency of using the developed standards. To establish patterns of dynamics of timber distribution by quality classes in oak stands further research is required.